PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN JIGSAW PADA MATERI POKOK ALJABAR KELAS VIII SMP NEGERI 21 SEMARANG TAHUN PELAJARAN 2010/2011 - HM Suyadi (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2011)
Mathematics from year to year is developing as more improvement as complicated era. The complicated era suggest men to be more creative to develop or to implement mathematics as a basic field. In Learning mathematics, students often feel it difficult to learn, besides that the learning process has not been understandable. So the students consider understanding on the concept falsely conseqnently the achievement frends to be lower either as individually or classically compared with other subjects. The problem taken in this research are.Whether implementing Jigsaw learning model can improve students learning ?, Wheter implementing Jigsaw learning model can improve the activity students on?é?á VIII grade, SMP Negeri 21 Semarang, education Year 2010/2011. On the basic algebra materials. Based on the test result from the cycle 1 and cycle II indicate that there is an improvement of learning. The student target mark increases classically from the cycle 1 to the cycle II. On the cycle 1, the passing grade mark mark classically on VIIIE SMP Negeri 21 Semarang is amount of 59,09%, it has not been fiil classical target mark. It is more than 85% but after implementing the class research on the cycle II, there is an?é?á improvement classical target mark to be 90,91% and has been over it classically to be more than 85%. Some suggest given by the researcher on the result of the research, one of them is on the learning process so the teacher should use learning method which is precisely for every topic learning taught. In this research for the main topic of effective algebra is used Jigsaw learning method. The teacher should give motivation on how importance learning to the student. So that they always have desires to study. The students should be ready by themselves to follow learning?é?á process in the classroom using some various learning methods which are different for cartain material on the activity of learning prosess so that it can be improved. Key Words: Learning Result, Jigsaw